2017
DOI: 10.3390/su9050830
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Rural Consumers on the Aspects of Meat Quality and Health Implications Associated With Meat Consumption

Abstract: This study was conducted to determine the perceptions of rural low-income consumers on meat quality and health issues associated with meat consumption. A total of 466 consumers in the Eastern Cape (EC) Province (South Africa (SA)) were randomly sampled, and principal component analyses (PCA) were used to analyse the data. With regard to purchasing decisions, correlation analysis was performed to establish the relationships between actual scores and mean scores so as to determine purchase motives and decisions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 38 publications
2
19
2
Order By: Relevance
“…This attribute, then, had low priority to be developed in purchasing decision. These findings are in accordance with previous study, arguing that packaging factor was not main determiner in purchasing decision by consumers, but beef's texture and price were deemed important to be considered by producers and marketers [20,21]. Nonetheless, this research is unlike with others investigation reporting that attribute of packaging was highly important to maintain beef's security, hygiene, and quality, so that its hygiene and security were well-protected to be consumed [22][23][24].…”
Section: Findings and Discussionsupporting
confidence: 92%
“…This attribute, then, had low priority to be developed in purchasing decision. These findings are in accordance with previous study, arguing that packaging factor was not main determiner in purchasing decision by consumers, but beef's texture and price were deemed important to be considered by producers and marketers [20,21]. Nonetheless, this research is unlike with others investigation reporting that attribute of packaging was highly important to maintain beef's security, hygiene, and quality, so that its hygiene and security were well-protected to be consumed [22][23][24].…”
Section: Findings and Discussionsupporting
confidence: 92%
“…Many consumers mostly buy raw chicken for preparation in their households at supermarkets, in a refrigerated or frozen state. In a similar South African study ( n = 466), Xazela, Hugo, Marume, and Muchenje (2017) also found that a high proportion of consumers from the Eastern Cape province (65%) most often buy meat at supermarkets. Supermarkets are most popular probably because they dominate about 65% of the South African meat market (Ncube, 2018).…”
Section: Purchasing and Consumption Habitsmentioning
confidence: 80%
“…Meat has become an important resource for human health; it has a high nutritional value, flavor, and juiciness characteristics [1]. In recent years, consumers and buyers have become more conscious of meat quality and safety [2].…”
Section: Introductionmentioning
confidence: 99%